2007
DOI: 10.1103/physrevd.76.104030
|View full text |Cite
|
Sign up to set email alerts
|

Loop quantum dynamics of the Schwarzschild interior

Abstract: We examine the Schwarzschild interior of a black hole, incorporating quantum gravitational modifications due to loop quantum gravity. We consider an improved loop quantization using techniques that have proven successful in loop quantum cosmology. The central Schwarzschild singularity is resolved and the implications for the fate of an in-falling test particle in the interior region is discussed. The singularity is replaced by a Nariai type Universe. We discuss the resulting conformal diagram, providing a clea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
304
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(325 citation statements)
references
References 25 publications
10
304
0
Order By: Relevance
“…For an exactly solvable model in LQC 4 , the properties of the spacetime across the bounce are almost identical 5 . Extension of these results on singularity resolution has been investigated for the black hole spacetimes [6][7][8][9][10] . It has been generally expected that as in the case of isotropic model in LQC, the spacetime after the bounce in the black hole interior shares very similar properties as the one before the bounce.…”
mentioning
confidence: 99%
“…For an exactly solvable model in LQC 4 , the properties of the spacetime across the bounce are almost identical 5 . Extension of these results on singularity resolution has been investigated for the black hole spacetimes [6][7][8][9][10] . It has been generally expected that as in the case of isotropic model in LQC, the spacetime after the bounce in the black hole interior shares very similar properties as the one before the bounce.…”
mentioning
confidence: 99%
“…Regarding the fact that the Planck densities and curvatures are the gates of the quantum gravity realm [38,39], These values of the density and curvature in the stable static phase imply that on the cusp of quantum gravity the pure semi-classical effects would become extremely important. As a matter of fact, in this paper we have shown that the resolution of singularity, which is a task relegated to appropriate quantum gravity theories [40][41][42], can also be attained by semi-classical methods like considering quantum vacuum effects on a curved background. In the following, we put a few remarks concerning some aspects and extensions of our considerations in order.…”
Section: Final Remarksmentioning
confidence: 99%
“…Efforts in order to find out black holes solutions in the context of LQG have been made by several authors [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In this work, we shall investigate the thermodynamics of a particular solution called the self-dual solution which was obtained by the use of loop quantum cosmology quantization techniques to the Schwarzschild scenario [39].…”
Section: Loop Quantum Black Holesmentioning
confidence: 99%